Possibilities for inclusion of Bulgarian protected areas on the IUCN Green List - Hristina Bancheva-Preslavska (Journal of the Bulgarian Geographical Society)
The most successful approach to conserving biodiversity is the development of a worldwide network of protected areas that are effectively managed through various tools and criteria. The latest global project for management quality of protected areas is the IUCN Green List Standard. It offers an instrument for regular assessment and implementation of protected area management efficiency. Listed sites gain recognition as a good example in nature preservation, international promotion, know-how, access to and exchange of global expertise, support and financial resources for good conservation outcomes. Bulgaria has a well-developed network of protected areas and participates in international programs with several nature sites. Joining the Green List program could influence national policy and actions for further excellence of the national network and its effective management, as well confirm Bulgarian commitment to global conservation efforts. The aim of this study is to assess the possibilities for including sites from the Bulgarian protected areas network on the IUCN Green List, identifying sites, ready to complete the application phase and be credible candidates for inscription. A review of the Bulgarian protected areas network was done and an evaluation, corresponding to the application phase of the Green List, of 49 natural sites (three national parks, 11 nature parks and 35 managed reserves) showed that the best potential candidates for the Green List are the administrations of Central Balkan National Park, Bulgarka Nature Park, Persina Nature Park and Belasitsa Nature Park. It is recommended that they start an application procedure and join the IUCN network.